Social Action Effects: Representing Predicted Partner Responses in Social Interactions - Neszmélyi, Bence; Weller, Lisa; Kunde, Wilfried; Pfister, Roland (Frontiers in Human Neuroscience, 2022)
The sociomotor framework outlines a possible role of social action effects for human action control, suggesting that anticipated partner reactions are a major cue to represent, select, and initiate own body movements. Here, we review studies that elucidate the actual content of social action representations and that explore factors that can distinguish action control processes involving social and inanimate action effects. Specifically, we address two hypotheses on how the social context can influence effect-based action control: First, by providing unique social features such as body-related, anatomical codes, and second, by orienting attention towards any relevant feature dimensions of the action effects. The reviewed empirical work presents a surprisingly mixed picture: While there is indirect evidence for both accounts, previous studies that directly addressed the anatomical account showed no signs for the involvement of genuinely social features in sociomotor action control. Furthermore, several studies show evidence against the differentiation of social and non-social action effect processing, portraying sociomotor action representations as remarkably non-social. A focus on enhancing the social experience in future studies should therefore complement the current database to establish whether such settings give rise to the hypothesized influence of social context.